Answer:
5n
Step-by-step explanation:
Answer:
(x, y ) = (3 , - 4 )
Step-by-step explanation:
given the 2 equations
2x - 3y = 18 → (1)
4x + y = 8 → (2)
multiply (2) by 3
12x + 3y = 24 → (3)
add (1) and (3) term by term to eliminate the term in y
(2x + 12x) + (- 3y + 3y) = (18 + 24)
14x = 42 ( divide both sides by 14 )
x = 3
substitute x = 3 in (1) or (2) to evaluate for y-coordinate
(2) → 12 + y = 8 ⇒ y = 8 - 12 = - 4
solution is (3, - 4 )
Answer:
41
Step-by-step explanation:
The n th term of an arithmetic sequence is
= a₁ + (n - 1)d
where a₁ is the first term and d the common difference
Here a₁ = - 7 and d = 3, thus
= - 7 + (16 × 3) = - 7 + 48 = 41
Answer:
Im in 8th! Hello there!
Step-by-step explanation:
The sum of your data set is 23.8333333333.All you have to do is add them all together and then divide by 6, which is the number of numbers there are.
8+13+17+26+32+47=143
143/6+23.8333333333